Description of Protosticta khasia sp. nov. and Yunnanosticta siangi sp. nov., with new records of P. samtsensis Gurung & Phan, 2023 from Northeast India (Odonata: Zygoptera: Platystictidae) - Joshi, Shantanu; Sarkar, Vivek; Sawant, Dattaprasad; Pawar, Ujwala; Kunte, Krushnamegh (Zootaxa, 2024)
Protosticta Selys is a genus of damselflies of the family Platystictidae Kennedy found in forests of tropical Southeast Asia. The genus Protosticta has rarely been reported from Northeast India. In this paper, we describe Protosticta khasia sp. nov. (subfamily Protostictinae Dijkstra et al.) based on holotype male and paratype female collected from Maraikaphon, East Khasi Hills district, Meghalaya, India. Protosticta khasia can be identified by the markings of the prothorax and the shape of the male paraproct with two arms. We also describe Yunnanosticta siangi sp. nov. (subfamily Sinostictinae Wilson) from Arunachal Pradesh, India, based on two males and two females. This species is differentiated from its congeners by the thoracic and abdominal markings as well as the shape of male caudal appendages. The key for males of Yunnanosticta is provided. Additionally, we provide new records of Protosticta samtsensis Gurung & Phan, along with an updated key to the Protosticta species of Northeast India.